Nocturnal landscape an evaluation on the functionality of urban landscape development for nighttime use - Navarra, Nappy L. (College of Architecture, University of the Philippines Diliman, 2009)
Today's society has evolved to become a complicated organization of relationships and complex urban forms. This scenario resulted to an environment that pulsates constantly, a routine that created stress and fatigue among urban dwellers. Globalization has further aggravated the situation that resulted to longer work hours spent inside the confines of office spaces, shorter vacation periods, less time for recreation, and more competitive and stressful environment for workers and their families. Massive urbanization and stressful environment in cities have divorced people from nature, making them ambivalent to its current state and unappreciative of the benefits of being in the outdoors. Opportunities to experience nature and the outdoors became visual and/or limited to simulated level. The research aims to examine and evaluate existing recreational and open spaces to determine their viability beyond the demands of daytime use. Nocturnal experience is quite different from diurnal experience since visual perception is limited while other senses are heightened. Security and accessibility become a bigger issue since vision is partially and temporarily impaired. Vegetation and hardscape colors become muted while artificial sources of light cast a different glow on different surfaces and textures. Nature, some of which has adapted to hibernating during daytime, becomes alive. The daytime memory of the same landscape spaces overlays with the new nocturnal experience, causing a juxtaposition of the same elements experienced in different time element. The research intends to measure observations and experiences of park users, and translate them into guidelines that would serve as a basis in designing landscape spaces that accommodates nocturnal functions and processes. The experience is differentiated into various dimensions : security and accessibility, perception, imageability, and accommodation of ecological processes.